EPIDEMIOLOGY OF CYRPTOSPORIDIUM IN APPARENTLY HEALTHY SHEEP IN SOUTHERN KHYBER PAKHTUNKHWA, PAKISTAN - N. U. Khan; M. H. Saleem; A. Z. Durrani; N. Ahmad; A. Hassan; M. Shafee; I. U. Khan; M. A. Khan; S. Zaman; A. U. Khan; N. Ullah; A. Razzaq; et al. (Journal of Animal and Plant Sciences, 2019)
Cryptosporidium is a prevalent enteric zoonotic parasite of domestic and wild animals, reptiles, birds and fish. This study was conducted to find out the prevalence and risk factors associated with the Cryptosporidium in apparently healthy sheep (Ovis aries), in three districts of Khyber Pakhtunkhwa (KPK), Pakistan. From January 2016 to December 2016, 1080 fecal samples were screened for the presence of Cryptosporidium oocysts through microscopy of smears stained by modified Ziehl-Neelsen technique. Results showed an overall prevalence of 17.96% (194/1080). The highest prevalence was recorded in Kohat (19.72%), followed by Bannu (18.61%) and Lakki Marwat (15.15%). Season-wise prevalence showed significant difference (P≤0.05) among different seasons, with highest prevalence during summer (25%), followed by spring (19.44%), autumn (17.72%) and the winter (10.55%). Statistical analysis revealed significant difference (P≤0.05) among sheep of different age groups with highest prevalence in newborns to ≤1 years of age (22.38%), followed by those of 1-2 years of age (18.03%) and more than 2 years of age (13.46%). Non-significant higher prevalence was recorded in females (18.80%) than males (17.02%). This debut study of Cryptosporidium in sheep will help designing disease control measures, as asymptomatic sheep is the key source of infection transmission to humans.
Keywords: Asymptomatic; Cryptosporidium; Epidemiology; Pakistan; Sheep